The Adenosinergic Signaling: A Complex but Promising Therapeutic Target for Alzheimer’s Disease - Cellai, Lucrezia; Carvalho, Kevin; Faivre, Emilie; Deleau, Aude; Vieau, Didier; Buée, Luc; Blum, David; Mériaux, Céline; Gomez-Murcia, Victoria (Frontiers in Neuroscience, 2018)
Alzheimer’s disease (AD) is the most common neurodegenerative disorder in elderly people. AD is characterized by a progressive cognitive decline and it is neuropathologically defined by two hallmarks: extracellular deposits of aggregated β-amyloid (Aβ) peptides and intraneuronal fibrillar aggregates of hyper- and abnormally phosphorylated Tau proteins. AD results by multiple genetic and environmental risk factors. Epidemiological studies reported beneficial effects of caffeine, a non-selective adenosine receptors antagonist. In the present review, we discuss the impact of caffeine and of adenosinergic system modulation on AD, in terms of pathology and therapeutics.